'Mind maps': helping from pedagogy to packing. Issue 4 (27th July 2016) - Dickinson, Ian
Abstract : A straw poll at the recent Royal Society of Medicine Winter Meeting in Saalbach, Austria, showed that only a handful of delegates were aware of 'mind maps' – surprising given that an internet search will find millions of mind map images and articles. In this article the author describes the basic concept of mind maps and how they can be used by healthcare professionals in their work.